2011
DOI: 10.2136/sssaj2010.0453
|View full text |Cite
|
Sign up to set email alerts
|

Massive Intercalation of Urea in Montmorillonite

Abstract: Urea intercalated in montmorillonite (MMT) leads to considerable improvement of N efficiency in soils; however, there are no systematic approaches to elucidate the properties of urea intercalates within the interlayer space of swelling clays. This study focused on both the optimization of massive urea intercalation into MMT and the systematic characterization of urea-intercalated MMT (UCM). Anhydrous metal salts, which could allow optimal urea intercalation, were used for the first time to synthesize metal-ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Recently, we developed a new type of N fertilizer (hereafter referred to as MUCH) intercalating massive urea in interlayer space of montmorillonite (MMT). It showed a high N efficiency through smart suppression of ammonia volatilization without any changes in its inheritable character, fast effectiveness (Kim et al, 2011a;Kim et al, 2011b). Furthermore, we confirmed that physicochemical properties of soils were not significantly affected by MUCH treatment in sandy loam and clay loam soils on column experiment (Kim et al, 2011c).…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Recently, we developed a new type of N fertilizer (hereafter referred to as MUCH) intercalating massive urea in interlayer space of montmorillonite (MMT). It showed a high N efficiency through smart suppression of ammonia volatilization without any changes in its inheritable character, fast effectiveness (Kim et al, 2011a;Kim et al, 2011b). Furthermore, we confirmed that physicochemical properties of soils were not significantly affected by MUCH treatment in sandy loam and clay loam soils on column experiment (Kim et al, 2011c).…”
Section: Introductionsupporting
confidence: 61%
“…Incorporation of citric acid into MUCH was confirmed by the existence of COO -symmetric stretching vibration at 1401 cm -1 as shown (Marchewaka and Pieraszko, 2003). Its IR spectrum also exhibited the red shift of >C=O and NH2 vibration energy and the blue shift of -C-N vibration energy as MUCH did (Kim et al, 2011a;Kim et al, 2011b). These IR bands are originated from urea molecules such as CO, NH2 and CN vibration energy at 1685, 1632 and 1468 cm -1…”
Section: Characterization Of Cit-much To Decrease Ph Ofmentioning
confidence: 84%
See 3 more Smart Citations